Lectin receptor kinases in plant innate immunity - Singh, Prashant; Zimmerli, Laurent (Frontiers in Plant Science, 2013)
A key feature of innate immunity is the ability to recognize and respond to potential pathogens in a highly sensitive and specific manner. In plants, the first layer of defense is induced after recognition by pattern recognition receptors of microbe-associated molecular patterns. This recognition elicits a defense program known as pattern-triggered immunity. Pathogen entry into host tissue is a critical early step in causing infection. For foliar bacterial pathogens, natural surface openings such as stomata, are important entry sites. Stomata in contact with bacteria rapidly close and can thus restrict bacterial entry into leaves. The molecular mechanisms regulating stomatal closure upon pathogen perception are not yet well understood. Plant lectin receptor kinases are thought to play crucial roles during development and in the adaptive response to various stresses. Although the function of most plant lectin receptor kinases is still not clear, a role for this kinase family in plant innate immunity is emerging. Here, we summarize recent progresses in the identification of lectin receptor kinases involved in plant innate immunity. We also discuss the role of lectin receptor kinases in stomatal innate immunity signaling.